The role of Inorganic Compounds in Membrane Technology for Seawater Desalination: Mini Review - Faqih, Shohibul (Indonesian Journal of Green Chemistry, 2024)
This mini-review article aims to explore the role of inorganic compounds in membrane technology applied to seawater desalination, with a focus on improving the performance and efficiency of the salt separation process. An integrative review method is used to collect and synthesize recent studies that identify various inorganic compounds, such as metal oxides and zeolites, that play important roles in the modification and development of desalination membranes. This review highlights the advantages and challenges of each inorganic compound in supporting the improvement of selectivity, permeability, and fouling resistance of membranes. By synthesizing the existing literature, this article provides a holistic view of how inorganic compounds can be optimized for energy efficiency and environmental sustainability in desalination technologies. These findings have the potential to provide direction for further research aimed at improving membrane quality and durability, which is urgently needed to face the challenges of clean water availability in the future.